Effects of continuous use of probiotics before liver transplantation: A randomized, double-blind, placebo-controlled trial. Issue 6 (December 2017) - Grąt, Michał; Wronka, Karolina M.; Lewandowski, Zbigniew; Grąt, Karolina; Krasnodębski, Maciej; Stypułkowski, Jan; Hołówko, Wacław; Masior, Łukasz; Kosińska, Irena; Wasilewicz, Michał; Raszeja-Wyszomirska, Joanna; Rejowski, Sławomir; et al.
Summary: Background & aims: Although there is increasing evidence for the benefits of probiotics in patients with liver diseases, data on the benefits of pre-LT administration of probiotics are lacking. The aim of this study was to evaluate the effects of continuous administration of probiotics before liver transplantation (LT) on pre- and post-transplant patient outcomes. Methods: In this randomized, double-blind, and placebo-controlled trial adult cirrhotic patients listed for LT received a 4-strain probiotic preparation or placebo daily from enrollment until LT. The primary outcome measures were postoperative mortality and infection rates. The secondary outcome measures were 5-day post-transplant aspartate and alanine aminotransferase activities, bilirubin concentration, and international normalized ratio; waiting-list mortality; pre-transplant Model for End-stage Liver Disease score and Child-Turcotte-Pugh class changes; and pre-transplant infections. Results: A total of 55 patients were randomized. The 90-day postoperative mortality rates were 0% and 4.3% in the probiotic and placebo groups, respectively (p > 0.99). Patients receiving probiotics had significantly reduced 30-day (4.8% versus 34.8%, p = 0.02) and 90-day (4.8% versus 47.8%, p = 0.002) infection rates, lower post-LT bilirubin concentration (p = 0.02), and more rapid decrease of aspartate (p = 0.03) and alanine (p = 0.03) aminotransferase activities. Probiotics did not have significant effects on other secondary outcome measures. Conclusions: Although continuous administration of probiotics before LT does not appear to affect postoperative mortality, it effectively prevents postoperative infections and improves early biochemical parameters of allograft function. ClinicalTrials.gov Identifier: NCT01735591 .